The Effect of Career Development Training on Nurse Performance at Datu Beru Takengon Hospital - Tarigan, Rahmawati; Hayati, Syafdina Ismie; Syafitri, Mei Elisa (Journal of Midwifery and Nursing, 2024)
Performance issues are currently a serious concern for every agency. Good performance will certainly guarantee excellent service quality. Companies can take various ways to improve the performance of their employees, including through training and career development. From the initial survey conducted at Datu Beru Takengon Regional Hospital, researchers found 2 officers in the training section who explained that training at the hospital had not been running for the last three years. Apart from that, there are still obstacles in the career development system due to the lack of optimal support from leadership and the varying implementation of career paths for nurses who do not understand the career path system well. Objectives; The aim of this research is to determine the relationship between training and career development and the performance of nurses at Datu Beru Takengon Regional Hospital. Method; This type of research uses a quantitative design with a cross-sectional design. The research population was all 236 nurses with a sample of 33 people taken using a purposive sampling technique. Data analysis used univariate and bivariate analysis with chi-square test statistics. Results; The research results show that the p value for the training variable = 0.004 < ? = 0.05 and career development = 0.000 < ? = 0.05, which means that training increases career development and performance for nurses at Datu Beru Takengon Regional Hospital. Conclusion; The research conclusion is that there is an influence of training on career development and performance of nurses at RSUD Datu Beru Takengon. It is recommended that hospitals hold training more frequently for career development as well as to improve the performance of nurses.